Recruitment patterns of six species of cyprinid fishes in the lower River Trent, England - Nunn, A. D.; Cowx, I. G.; Harvey, J. P. (ECOLOGY OF FRESHWATER FISH, 2002)
Fisheries data were collected for six species of 0-group cyprinid fishes from eight sites in the lower reaches of the River Trent, England, between May and October 1999 inclusive, using a micromesh seine net. Recruitment and growth patterns were observed via monthly length-frequency histograms and estimations of mean length. In the cases of roach and dace, growth was approximately linear through the summer, before declining in September and October. In the cases of chub and gudgeon, and to a lesser extent bream and bleak, however, there were suggestions of multiple recruitment events. It is argued that some of the fish species examined in the present study adopt fractional or protracted spawning strategies in the lower River Trent.
Output ID 21645.
Keywords: Recruitment; Juvenile growth; Fractional spawning; Protracted spawning; Cyprinid fishes